Internal family systems as an eco‐spirituality model: Hearing the cries, confrontation, and call from Covid‐19. Issue 4 (31st January 2022) - Baldwin, Jennifer L.
Abstract: This article explores the potential of Internal Family Systems as a spiritual practice that can guide human responses to restoring right relationship as species on the planet. It problematizes the centralizing of the coronavirus in human experiences and argues for an awareness of the pandemic within the larger context of climate change. It then offers encouragement to return to an honoring of indigenous wisdom and communities as the true care tending elders of the planet as well as the ritualized therapeutic practice of IFS as a lens for gaining clarity on the roles each of us fall into in times of threat. Finally, this article invites us to envision how we collectively got to this place of suffering, our patterns that perpetuate suffering, and a hope to move forward with compassionate and courageous clarity.